Cities and urban consumption in transition towards sustainability - Mauro ROMANELLI (Smart Cities and Regional Development Journal)
Sustainable urban development is advancing through cities that aim at encouraging sustainable consumption behaviours. Cities are in transition to achieving urban sustainability, meeting the needs of communities without compromising the wealth of future generations. Cities are playing a leading role in advancing towards sustainable urban consumption, and enabling citizens as responsible consumers and agents of social change. Driving responsible urban consumption provides benefits to urban communities by ensuring a better quality of life of people within urban spaces and natural environments. The future of urban development relies on promoting styles and behaviours of responsible consumption and making healthy and environment-friendly urban spaces.